2018
DOI: 10.3390/ijms19123991
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics Analysis Reveals That Caspase-Like and Metacaspase-Like Activities Are Dispensable for Activation of Proteases Involved in Early Response to Biotic Stress in Triticum aestivum L.

Abstract: Plants, including Triticum aestivum L., are constantly attacked by various pathogens which induce immune responses. Immune processes in plants are tightly regulated by proteases from different families within their degradome. In this study, a wheat degradome was characterized. Using profile hidden Markov model (HMMer) algorithm and Pfam database, comprehensive analysis of the T. aestivum genome revealed a large number of proteases (1544 in total) belonging to the five major protease families: serine, cysteine,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 74 publications
0
6
0
Order By: Relevance
“…Peptidase M24 proteins superfamily members have multiple biological functions in animals, plants, and microorganisms, and are an emerging gene family. In plants, the functions of most members of the peptidase M24 superfamily are not known in detail, but studies have shown that these genes are involved in a variety of biological processes, such as participating in the protein synthesis process [25,29,[48][49][50][51], ensuring the normal development of plant organs [14,28,32,52,53], regulating the formation of special structures in legumes [54], abiotic response and biotic stress [15,16,34,54]. Therefore, this study aimed to identify and classify the members of the peptidase M24 in wheat, explore the role of TaM24 genes in drought and salt stress in Arabidopsis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Peptidase M24 proteins superfamily members have multiple biological functions in animals, plants, and microorganisms, and are an emerging gene family. In plants, the functions of most members of the peptidase M24 superfamily are not known in detail, but studies have shown that these genes are involved in a variety of biological processes, such as participating in the protein synthesis process [25,29,[48][49][50][51], ensuring the normal development of plant organs [14,28,32,52,53], regulating the formation of special structures in legumes [54], abiotic response and biotic stress [15,16,34,54]. Therefore, this study aimed to identify and classify the members of the peptidase M24 in wheat, explore the role of TaM24 genes in drought and salt stress in Arabidopsis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the gene expression of the Ammopiptanthus mongolicus EBP1 gene (AmEBP1) increases continuously under salinity stress over 48 h. AtAPP1 can also interact with superoxide dismutase (SOD), POD and E2-ubiquitin-conjugating enzymes in response to hormone signalling [32,33]. In addition, another study showed that the initial immune response to biotic stress was related to the same core proteases from C1, C48, C65, M24, M41, S10, S9, S8, and A1 families in wheat [34].…”
Section: Introductionmentioning
confidence: 99%
“…Among the genes found were zinc finger A20 and AN1 domain-containing stress-associated protein 3, stress response protein NAC SECONDARY WALL THICKENING PROMOTING FACTOR1 (NST1), heat stress TF A-5-like, abscisic stress-ripening protein 1-like, ERF036, ERF061, ERF104, ERF RAP2-13, ETHY-LENE INSENSITIVE 3-like, cold-responsive protein kinase 1-like, heat shock proteins including HSP70, HSP80, and HSP90. These genes are primarily involved in different stress signaling and regulation processes (Giri et al, 2011;Mitsuda et al, 2005;Bourgine and Guihur, 2021;Müller and Munné-Bosch, 2015;Balakireva et al, 2018).…”
Section: Characterization Of Ssrsmentioning
confidence: 99%
“…Based on this data, we believe that death-inducing cascades do exist in plants and their participants are different in origin, but similar in function. Recently, it was used for the identification of sites of hydrolysis by endogenous proteases during biotic stress (Balakireva et al, 2018). It was shown that during the early response of wheat to different pathogens, caspase-like and metacaspase-like activities are not required, while immune response is still triggered and, apparently, is held by some other proteases, which confirms our assumptions in a way.…”
Section: Transduction Of a Signal: Which Proteolytic Cascades Exist Imentioning
confidence: 99%